Synergistic effect of oil cakes and Trichoderma asperellum in the suppression of Sclerotium rolfsii - S.S. Veena; P. Neethu Krishna; S. Karthikeyan (JOURNAL OF ROOT CROPS, 2024)
Root and tuber crops are important as principal staple and nutritive foods for human beings. They are mainly used as food, animal feed and in industries. The tropical tuber crops are susceptible to many pathogens in field as well as in storage which lead to significant economic loss. Elephant foot yam (EFY) (Amorphophallus paeoniifolius) is a highly preferred crop in tropical and sub-tropical regions due to its high production potential (50–80 t ha-1), market acceptability and lucrative economic returns. In organic cultivation of EFY, many growers practice incorporation of oil cakes to soil and use bio-agent, Trichoderma to enhance crop health and to reduce collar rot incidence. Collar rot caused by Sclerotium rolfsii is the most destructive and predominant disease, which causes significant crop loss. In the present study, oil cakes of coconut, groundnut, neem, mustard and sesame were evaluated in sterile and unsterile conditions for their ability to suppress S. rolfsii. The ability of oil cakes to support the growth and sporulation of Trichoderma asperellum was also studied. All the oil cakes completely inhibited the growth of S. rolfsii. When the concentration of oil cakes was reduced to 50% by diluting it with soil, sesame and groundnut oil cakes could not arrest the mycelia growth. Except neem oil cake, pathogen suppression potential of all other cakes was reduced upon sterilization. It varied from 39.53% (mustard oil cake) to 87.44% (sesame oil cake). Under unsterile condition, mycelial growth of Trichoderma completely covered the substrates, neem and groundnut oil cakes, which turned to green due to the sporulation. No growth was observed in coconut oil cake while scanty growth without sporulation was noticed with mustard and sesame oil cakes. Upon sterilization, mycelial growth of Trichoderma completely covered all the substrates except coconut oil cake. Thus, neem oil cake is ideal for the organic cultivation of elephant foot yam since it suppresses the pathogen as well as promotes growth and proliferation of Trichoderma. Keywords: Elephant foot yam, Neem oil cake, Trichoderma, Sclerotium rolfsii, Mustard oil cake